2021
DOI: 10.1038/s41598-020-80588-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of small molecules targeting the tandem tudor domain of the epigenetic factor UHRF1 using fragment-based ligand discovery

Abstract: Despite the established roles of the epigenetic factor UHRF1 in oncogenesis, no UHRF1-targeting therapeutics have been reported to date. In this study, we use fragment-based ligand discovery to identify novel scaffolds for targeting the isolated UHRF1 tandem Tudor domain (TTD), which recognizes the heterochromatin-associated histone mark H3K9me3 and supports intramolecular contacts with other regions of UHRF1. Using both binding-based and function-based screens of a ~ 2300-fragment library in parallel, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Since UHRF1 is overexpressed in a wide variety of solid tumours and it is not required in non-replicating cells, its downregulation could be used to overcome the resistance to DNA damaging agents by impairing DNA repair mechanisms. While several approaches have been tested to inhibit the different domains of UHRF1 ( 149 , 150 ), a recent work focused specifically on targeting UHRF1 functions in DNA damage repair ( 151 ). Here it is shown that in prostate cancer cells, the combined treatment with HDAC and PARP inhibitors (SAHA and veliparib) disrupts the interaction between UHRF1 and BRCA1 and decreases UHRF1 and BRCA1 levels, resulting in inhibition of the HR pathway and cell death ( 151 ).…”
Section: Uhrf1 In Dna Damage Response As a Potential Therapeutic Targetmentioning
confidence: 99%
“…Since UHRF1 is overexpressed in a wide variety of solid tumours and it is not required in non-replicating cells, its downregulation could be used to overcome the resistance to DNA damaging agents by impairing DNA repair mechanisms. While several approaches have been tested to inhibit the different domains of UHRF1 ( 149 , 150 ), a recent work focused specifically on targeting UHRF1 functions in DNA damage repair ( 151 ). Here it is shown that in prostate cancer cells, the combined treatment with HDAC and PARP inhibitors (SAHA and veliparib) disrupts the interaction between UHRF1 and BRCA1 and decreases UHRF1 and BRCA1 levels, resulting in inhibition of the HR pathway and cell death ( 151 ).…”
Section: Uhrf1 In Dna Damage Response As a Potential Therapeutic Targetmentioning
confidence: 99%
“…Considering the number of structurally unique protein domains required to coordinate DNA repair on chromatin, it is not surprising that many small molecule inhibitors are available that are potentially capable of disrupting the functions of these domains ( Arrowsmith and Schapira, 2019 ; Mio et al, 2019 ). Chemical or peptide based inhibitors have recently been developed to target several domains that are found within DDR proteins including tandem tudor domains ( Chang L. et al, 2021 ), PRC1 chromodomains ( Stuckey et al, 2016 ), PHD zinc fingers ( Wagner et al, 2012 ), bromodomains ( Filippakopoulos et al, 2010 ) and ubiquitin interacting motifs (UIM) ( Manczyk et al, 2019 ). In addition to their potential clinical applications, the development and availability to researchers of specific inhibitors of these repair-chromatin interactions will be advantageous for untangling and defining the specific contribution of individual contacts within these proteins and their ability to mediate DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been great interest in identifying compounds that target UHRF1 as potential anticancer agents 42–46 . The mechanism of action of several of these compounds involves disrupting the histone binding activities of the TTD or TTD‐PHD domains 44–46 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been considerable interest in UHRF1 as a therapeutic target via inhibiting its DNA and histone reader function through small molecule inhibition 8,42–46 . In particular, several compounds have been identified using high throughput screening strategies that disrupt the histone binding activities of the TTD and TTD‐PHD 44–46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation